2008
DOI: 10.1002/hep.22351
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal endothelial cells prevent rat stellate cell activation and promote reversion to quiescence

Abstract: Capillarization precedes hepatic fibrosis. We hypothesize that capillarization of sinusoidal endothelial cells (SEC) is permissive for hepatic stellate cell (HSC) activation and therefore permissive for fibrosis. We examined whether freshly isolated SECs prevent activation of HSCs and promote reversion to quiescence, and whether this effect was lost in capillarization. HSCs were cultured alone or co-cultured with differentiated or capillarized SECs. Results: Co-culture with freshly isolated SECs markedly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
298
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(311 citation statements)
references
References 41 publications
11
298
0
2
Order By: Relevance
“…Hepatic VEGF mRNA expression is significantly increased in the rat model in parallel with sinusoidal damage (44) and serum VEGF increase correlates with the development of SOS in patients after hematopoietic stem cell transplantation (45). VEGF plays a major role in maintaining SEC differentiation (46)(47)(48). The increased expression of VEGF could therefore be a response to endothelial barrier disruption or to cellular hypoxia following SOS.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic VEGF mRNA expression is significantly increased in the rat model in parallel with sinusoidal damage (44) and serum VEGF increase correlates with the development of SOS in patients after hematopoietic stem cell transplantation (45). VEGF plays a major role in maintaining SEC differentiation (46)(47)(48). The increased expression of VEGF could therefore be a response to endothelial barrier disruption or to cellular hypoxia following SOS.…”
Section: Discussionmentioning
confidence: 99%
“…NO production usually decreases, leading to an increasing intrahepatic pressure due to an inability to maintain intrasinusoidal autoregulation by vasodilatation [1,17]. In addition, decreased NO production activates a contractile phenotype of HSC, inducing extracellular matrix production and migratory capacity [18,19]. Finally, recent studies revealed the importance of angiogenesis in the process of fibrogenesis and their interdependency [12,20].…”
Section: Sinusoidal Endothelial Cellsmentioning
confidence: 99%
“…However, as described for SEC, HSC can undergo dramatic phenotype transformation in the context of liver injury: a decrease in NO production by SEC, which normally induces HSC quiescence, leads to HSC activation characterized by enhanced contractility, increased migratory capacity, deposition of extracellular matrix components such as fibronectin and collagen I or III, upregulation of smooth muscle alpha actin (a-SMA), and increased release of autocrine and paracrine factors. Besides this canonical NO pathway for quiescence and activation of HSC, [18,19] several other soluble factors from surrounding cells (such as hepatocytes, Kupffer-cells, and lymphocytes) play an important role in HSC activation [26]. Interestingly, studies of different extracellular matrices have revealed that matrix stiffness itself is a key determinant of HSC activation, although involved proteins and receptors have not been identified so far [27].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
See 2 more Smart Citations